2013
DOI: 10.1177/1534650113475701
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Exposure Therapy for Posttraumatic Nightmares

Abstract: Nightmares are one of the most troubling features of posttraumatic stress disorder (PTSD), yet imagery rehearsal training (IRT) is currently the only empirically supported treatment for posttraumatic nightmares. Although IRT is effective, it is unknown whether IRT or the exposure, which is inherent in this procedure, causes the decrease in nightmares. This study will attempt to clarify this issue by using exposure therapy alone to treat a patient with PTSD. The participant is a 39-year-old male who experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Post-traumatic stress disorder symptoms were assessed pre and post intervention in all but four studies (Blunden, 2017;Cavera et al, 2013;Davis et al, 2003;Thünker & Pietrowsky, 2012). In DeViva et al (2005), all five participants lost their diagnosis of PTSD following the sleep intervention, PTSD diagnoses dropped from 53% at pre-treatment to 21% at 6-month follow-up in Davis and Wright (2007), one child participant in Fernandez et al (2013) lost her diagnosis of PTSD, and 75% of participants lost their diagnosis at 6-month follow-up in In several studies (Belleville et al, 2018;Germain et al, 2007;Krakow et al, 2001;Miller et al, 2018;Talbot et al, 2013), treatment groups saw significant reductions in PTSD symptom severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-traumatic stress disorder symptoms were assessed pre and post intervention in all but four studies (Blunden, 2017;Cavera et al, 2013;Davis et al, 2003;Thünker & Pietrowsky, 2012). In DeViva et al (2005), all five participants lost their diagnosis of PTSD following the sleep intervention, PTSD diagnoses dropped from 53% at pre-treatment to 21% at 6-month follow-up in Davis and Wright (2007), one child participant in Fernandez et al (2013) lost her diagnosis of PTSD, and 75% of participants lost their diagnosis at 6-month follow-up in In several studies (Belleville et al, 2018;Germain et al, 2007;Krakow et al, 2001;Miller et al, 2018;Talbot et al, 2013), treatment groups saw significant reductions in PTSD symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements were also reported for sleep quality, decreased impairment resulting from sleep difficulty, and fear of sleep (DeViva et al, 2005) and PTSD symptom severity (Germain et al, 2007). Prolonged exposure therapy was successful in reducing the frequency and severity of NMs for one participant in Cavera et al (2013) and upon pre and post examination of sleep diary data, results of the "Boss of my sleep intervention" (Blunden, 2017) showed positive improvements for the child. Specifically, he began sleeping every night in his own bed, NWs decreased from 5.2 (avg) to 0, DSO, decreased from 35-min (avg) to 10-min, wake time increased from 5:05 a.m. (avg)…”
Section: Single Case Research Designsmentioning
confidence: 96%
“…The utilization of exposure therapy as part of PTSD treatment has been shown to be effective for reducing trauma-related nightmares (Cavera et al, 2013). Nonetheless, many residual symptoms including nightmares can remain after evidence-based trauma-specific therapies (Larsen et al, 2019), therefore utilizing a nightmare-specific treatment in addition to PTSD therapies has been indicated (Waltman et al, 2018).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…NET has been indicated in several studies to be effective at decreasing PTSD symptoms 6 months following treatment, and eliminating symptoms in some individuals as little a year following treatment ; Onyut et al, 2005;Robjant & Fazel, 2010;van Minnen, Wessel, Dijkstra, & Roelofs, 2002). Cavera, Jacobs, and Motta (2012) indicated that exposure-based nightmare treatment for PTSD sufferers should be considered in conjunction with standard treatment packages. Fernandez et al (2013) reported improvement in trauma related nightmares in children related to PTSD using exposure, relaxation, and rescripting therapy.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Cavera, Jacobs, and Motta (2012) indicated that exposure-based nightmare treatment for PTSD sufferers should be considered in conjunction with standard treatment packages. Fernandez et al (2013) reported improvement in trauma related nightmares in children related to PTSD using exposure, relaxation, and rescripting therapy.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%